Endoscopic Endonasal Transpituitary Gland Approach for Resection of Dorsum Sellae Meningioma – Technical Case Report. Issue 6 (19th March 2019) - Ko, Yumi; Nishimura, Fumihiko; Park, Young-Soo; Motoyama, Yasushi; Nakagawa, Ichiro; Yamada, Shuichi; Tamura, Kentaro; Matsuda, Ryosuke; Takeshima, Yasuhiro; Takamura, Yoshiaki; Nakase, Hiroyuki
Abstract: BACKGROUND AND IMPORTANCE: Access to a dorsum sellae meningioma is difficult. A transcranial approach, such as a pterional, subtemporal, or transpetrosal method, often requires significant brain retraction and crossing of cranial nerves to access this region. We present here a successful purely endoscopic endonasal transpituitary gland approach for resection of a growing dorsum sellae meningioma. CLINICAL PRESENTATION: A 74-yr-old woman came to us with dizziness. Magnetic resonance imaging (MRI) demonstrated a mass on the dorsum sellae around the left posterior clinoid. Follow-up MRI examinations over a 3-yr period showed a gradual increase in size of the mass and increasing compression of the left peduncle. To avoid brain retraction, an endoscopic endonasal approach was selected for tumor removal. With this method, we went through the pituitary gland by splitting it, and drilled into the dorsum sellae and clivus to access the front of the tumor. Gross total removal was safely achieved. The patient was asymptomatic and had normal pituitary function after the operation. CONCLUSION: The present endoscopic endonasal transpituitary gland approach allowed for safe resection of a dorsum sellae meningioma. We consider it to be less invasive for patients because of no need for brain retraction.